2020
DOI: 10.1038/s41598-020-69019-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiovascular medications on primary patency of hemodialysis arteriovenous fistula

Abstract: While the patency of vascular access is essential for hemodialysis patients, optimal pharmaceutical treatment to maintain arteriovenous fistula (AVF) patency remains lacking. As cardiovascular diseases are highly prevalent in patients with end-stage renal disease, various cardiovascular medications have also been used to maintain AVF patency. However, previous studies revealed inconsistent therapeutic effects and a comprehensive evaluation of this issue is needed. The present retrospective, longitudinal cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A retrospective, longitudinal cohort study of AVF patients investigated the association between AVF primary patency and the use of antiplatelet agents, antihypertensive agents, nitrates and nitrites, statins, dipyridamole and pentoxifylline. Of these medications, only dipyridamole showed a significant association with a higher risk of AVF patency loss, in particular, when combined with antiplatelet agents 32…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective, longitudinal cohort study of AVF patients investigated the association between AVF primary patency and the use of antiplatelet agents, antihypertensive agents, nitrates and nitrites, statins, dipyridamole and pentoxifylline. Of these medications, only dipyridamole showed a significant association with a higher risk of AVF patency loss, in particular, when combined with antiplatelet agents 32…”
Section: Discussionmentioning
confidence: 99%
“…Of these medications, only dipyridamole showed a significant association with a higher risk of AVF patency loss, in particular, when combined with antiplatelet agents. 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single-center study including 349 patients with newly created AVFs also failed to identify the beneficial effect of RASBs on AVF patency. 2 In a study of 121 patients with AVG, Gradzki observed better primary access failure in patients with angiotensin-converting enzyme inhibitors than those without the drug. 12 Saran et al analyzed the data of the Dialysis Outcomes and Practice Patterns Study cohort including 900 AVF and 1944 AVG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the efficacy of some medications in improving vascular access-related outcomes; however, evidence of their efficacy is insufficient. 2,3 Renin-angiotensin system blockades (RASBs) are well-known blood pressure-lowering drugs. Previous studies have demonstrated their beneficial effects on cardiovascular system or vascular pathologies.…”
Section: Introductionmentioning
confidence: 99%